Tubular adenoma of the stomach with special reference to the Japanese criteria and pyloric gland adenoma Das tubuläre magenadenom: Mit darstellung der japanischen kriterien unter berücksichtigung des "pyloric gland adenoma" - Kushima, R.; Vieth, M. (Pathologe, 2010)
The term gastric adenoma usually refers to a flat adenoma of the intestinal type. Adenomas of the gastric type, so-called pyloric gland adenomas (PGA), which was first characterized by German and Japanese pathologists in 1990, have been regarded as exceptional until recently. In 2003, we first reported systematic clinical pathological analyses of PGA, demonstrating its unstable and precancerous nature. American gastrointestinal pathologists have finally recognized this disease entity in 2009. In this article we introduce the Japanese criteria of the gastric adenoma and review and discuss the clinical pathological and molecular aspects of PGAs. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Gastric type; Intestinal type; Japanese criteria; Pyloric gland adenoma; Tubular adenoma